Hepatocellular carcinoma at the University of Puerto Rico Liver Transplant Clinic - Rivera-Resto, Michelle; De Varona-Negrón, Miguel; Eguía, Vasco; Carlo, Victor L.; Torres, Esther A. (Puerto Rico Health Sciences Journal, 2007)
The aim of this study was to determine the prevalence of hepatocellular carcinoma (HCC) in our liver transplant clinic, and describe the risk factors, predictors and treatment outcomes of primary liver cancer. Methods: 459 of 469 records of patients attending the UPR Liver Transplant Clinic from September 1999 to January 2005 were reviewed. Frequency distributions were computed to describe the study group. Results: 35 patients (7%) were included. 33 patients were diagnosed during the pre-transplant evaluation and 2 were diagnosed in the explant. Mean age at diagnosis in males was 54.5 years and 61.3 years in females. The main cause of liver disease was hepatitis C plus ethanolism in 42.9% (15 cases). The frequency of HCC in patients with a BMI > 25 Kg/m2 was more than twice that of patients with a BMI < 25 Kg/m2. Predominant presenting symptoms were ascites (40%), abdominal pain and jaundice (25%). Normal alphafetoprotein was found in 25%. 76% had a MELD score < 20. Treatment modalities included trans-arterial embolization (TAE/TACE) (49%), conservative treatment (34%), liver transplant (OLT, 23%), partial resection (9%) and systemic chemotherapy (3%). Eight patients underwent OLT and one developed primary graft failure, needing a second transplant. Two had T1N0M0 score, with a 100% survival at 2 yrs, and 6 patients had a T2N0M0 score, 5 of which underwent TAE before OLT, with an overall survival of 67%. Partial resection had an overall survival of 66%. Conclusions: The population of our clinic is similar in gender and age distribution, etiology of chronic liver disease, and clinical presentation of HCC to otherspreviously described. Our treatment outcomes and mortality rates compare with those observed in the literature.